2016
DOI: 10.1007/s10072-016-2637-3
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of multiple sclerosis among women in Buenos Aires: a 22 year health maintenance organization based study

Abstract: Studies in multiple sclerosis (MS) suggest a trend of increasing disease prevalence and incidence, and especially, a disproportional increase in the incidence of multiple sclerosis in women. The objective of this study was to evaluate the incidence of MS over 22 years and to determine the ratio in incidence of men to women in a health maintenance organization from Buenos Aires, Argentina. The population was made up of all members of a hospital-based HMO affiliated between January 1992 and December 2013. Each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Regarding incidence, we found five studies (French West Indies, Argentina and Panama) that evaluated this issue. 16,19,24,38 Of these five studies, one reported incidence from a period of 16 years that was later extended to 22 years. This study identified an increase in incidence during the follow-up period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding incidence, we found five studies (French West Indies, Argentina and Panama) that evaluated this issue. 16,19,24,38 Of these five studies, one reported incidence from a period of 16 years that was later extended to 22 years. This study identified an increase in incidence during the follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…This study identified an increase in incidence during the follow-up period. 38 Incidence values ranged from 0.15 to 3 annual cases per 100,000 person-years (Table 1). Regarding prevalence rates, 13 identified studies assessed prevalence in the region (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, whether MS is an emerging disease among Hispanic individuals is unclear yet appears plausible. This concern has been raised by multiple investigators and is supported by increasing MS incidence and prevalence in selected Latin American countries, 18 particularly Argentina 19 and Puerto Rico. 20 Our findings that MS prevalence is higher among young Hispanic adults than among young White adults yet significantly lower among older Hispanic adults compared to White adults residing in Southern California are consistent with emerging disease hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…MS affects individuals worldwide [ 118 ], and the underlying mechanism in disease development remains unclear. MS is a multifactorial disease associated with both genetic and environmental factors, such as vitamin D levels, ultraviolet B (UVB) exposure, Epstein–Barr infections (EBV), pollution, obesity, and smoking, increase the risks of developing MS [ 119 ]. MS is traditionally considered an autoimmune disease associated with T cell activity.…”
Section: Recent Advances In the Treatment Of Neurological Disordermentioning
confidence: 99%